Amelioration effect of Lactobacillus plantarum KFY02 on low-fiber diet-induced constipation in mice by regulating gut microbiota - Yi, Ruokun; Zhou, Xin; Liu, Tongji; Xue, Rui; Yang, Zhennai (Frontiers in Nutrition, 2022)
This study aimed to examine the ameliorating effect of Lactobacillus plantarum (LP) KFY02 on low-fiber diet-induced constipation in mice. LP-KFY02 was isolated from the natural fermented yogurt in Korla of Xinjiang. The mice with low-fiber diet-induced constipation in experimental groups were administered 1×109 CFU/kg LP-KFY02 (KFY02H) and 1×108 CFU/kg LP-KFY02 (KFY02L). After LP-KFY02 treatment with constipation mice, the mice fecal water content, intestinal transit ability and defecation time of constipated mice were improved. The mice fecal flora diversity, abundance and structure of the intestinal flora were regulated to the balanced state. The mice serum levels of gut motility related neuroendocrine factors have been increased, the intestinal mucosal barrier function and gut motility related gene expression were regulated in mice colon tissues. At the same time, the mice colon tissue damage were improved. These parameters in the KFY02H group were close to the normal group. These results suggested that LP-KFY02 could be considered as a potential probiotic to help alleviate low-fiber diet-induced constipation. They also provided a theoretical basis for the study of probiotics to relieve constipation by regulating intestinal flora.